Klebsiella variicola: an emerging pathogen in humans - Nadia Rodríguez-Medina; Humberto Barrios-Camacho; Josefina Duran-Bedolla; Ulises Garza-Ramos (Emerging Microbes and Infections)
The Klebsiella pneumoniae complex comprises seven K. pneumoniae-related species, including K. variicola. K. variicola is a versatile bacterium capable of colonizing different hosts such as plants, humans, insects and animals. Currently, K. variicola is gaining recognition as a cause of several human infections; nevertheless, its virulence profile is not fully characterized. The clinical significance of K. variicola infection is hidden by imprecise detection methods that underestimate its real prevalence; however, several methods have been developed to correctly identify this species. Recent studies of carbapenemase-producing and colistin-resistant strains demonstrate a potential reservoir of multidrug-resistant genes. This finding presents an imminent scenario for spreading antimicrobial resistant genes among close relatives and, more concerningly, in clinical and environmental settings. Since K. variicola was identified as a novel bacterial species, different research groups have contributed findings elucidating this pathogen; however, important details about its epidemiology, pathogenesis and ecology are still missing. This review highlights the most significant aspects of K. variicola, discussing its different phenotypes, mechanisms of resistance, and virulence traits, as well as the types of infections associated with this pathogen.